The formation of subjective house price expectations - Sarah Kiesl-Reiter; Melanie Lührmann; Jonathan Shaw; Joachim Winter (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2024)
Subjective house price expectations drive individual housing choices and market dynamics. We study the formation of subjective expectations about local house prices using novel survey data from Britain, a country with high homeownership rates and widely varying local housing dynamics. There is a substantial and heterogeneous perception gap and individuals extrapolate strongly from perceived but not from realized past price changes. In addition, expectations are predicted by wider, easily observable measures of local economic conditions, especially among individuals with low financial sophistication. Individuals residing in local housing markets where past prices are less informative or less observable rely more strongly on local economic conditions in their belief formation. Our results emphasize the role of heterogeneity in expectations formation processes, and their underlying information set.
Keywords: D12; D84; 330; Subjective Expectations; Local Housing Markets; Local Economic Conditions